A Case study of the chapels of a funeral establishment in Quezon City in relation to the beliefs and funerary practices of Chinese-Filipino users - Cua, Dan Gabriel C.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
Abstract This case study identified the needs of the Chinese-Filipinos arising from their syncretic beliefs and practices in regards to death, wakes, and funerals (Dy, 2015). These needs were reflected and addressed in the funerary space that these people use as spiritual, intellectual, and material demands should be satisfied by the conception of architecture and interior design (Malnar & Vodvarka 1992). During the first phase, interviews in order to identify the said beliefs and practices were conducted among two groups of people: 1) key informants chosen from a purposive sample based on their expertise in the religions and the Chinese-Filipino culture, and 2) respondents chosen from a self-selected sample of Chinese-Filipinos who have visited a wake in a funeral establishment along Araneta Avenue. The second phase consisted of an ocular documentation of two chapels of a single funeral establishment along Araneta Avenue, chosen with purposive sampling based on verbatim responses from the first phase, to see how these beliefs and practices are reflected in the design of the said chapels. The case study focused on small sampling sizes which allowed the study to be in-depth and qualitative with the data gathered from interviews and ocular documentation. Five needs were identified based on the beliefs and practices of the Chinese-Filipinos as presented in the interviews namely: a solemn environment, space allocation for displaying paraphernalia, to have facilities where users can burn various paper paraphernalia, the space to be flexible in order to cater to social gatherings, and a space of privacy for the family of the deceased. Based on the ocular documentation, these needs were generally met with a few suggestions from the responses from the first phase. Findings from this study may aid current and future funeral establishment owners, as well as designers, in creating funeral spaces which can cater to the needs of the Chinese-Filipino. This may also be a point of discussion for people of different religious affiliations in creating spaces which may cater to people of varying faiths. As mentioned in the scope and limitations, there was focus given on the funeral chapels, a small sample size, and a specific geographical area due to the nature of the case study. Future studies with related topics may explore beyond this scope in data-gathering.
Submitted August 2018.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Funeral homes -- Philippines -- Quezon City; Chapels -- Decoration